Conceptual Approaches to the Study of the Role of International Investment as a Catalyst for Economic Development - Kozulin Vladyslav V. (Bìznes Inform, 2025)
The aim of the article is to explore and organize approaches to international investment and to emphasize its significant role in economic development. The author thoroughly examines the main theoretical models, including classical, neoclassical, and modern approaches, as well as relevant concepts such as the eclectic paradigm and the theory of competitive advantages of countries. Particular attention is paid to the mechanisms through which international investment contributes to the development of economies, including technology transfer, human capital development, and modernization of production. An important aspect of the research is to identify the key factors of investment attractiveness in contemporary economies, which include not only economic and political conditions but also the effectiveness of legal and regulatory processes, domestic economic activities, the capacity for technological innovations, and the ease of capital movement. Based on research, including the Kearney FDI Confidence Index for 2025, the factors influencing the choice of investment locations are analyzed, as well as the characteristics of attracting foreign direct investment in countries with varying levels of economic development. Examples from different regions of the world illustrate various aspects of attractiveness for investors. By substantiating theoretical models and contemporary empirical data, the research results highlight that international investment is a powerful catalyst for economic development, contributing not only to increased production efficiency but also to ensuring long-term stability of economies that become more competitive on a global scale. The conclusions present the results of the systematization of theories and approaches to international investment, providing a deeper understanding of the processes that promote economic development through the attraction of foreign direct investment (FDI). This also opens up new prospects for the development of effective investment attraction policies in developing countries, and provides useful recommendations for international companies seeking optimal investment directions in the context of global economic changes.